Pengaruh Jenis Media Tanam dan Varietas terhadap Hasil Tanaman Melon (Cucumis melo L.) pada Sistem Irigasi Tetes - INDRAWAN, I KADEK AGUS; GUNADI, I GUSTI ALIT; WIRAATMAJA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.3, Juli 2021, 2021)
The Effect of Planting Media and Varieties on the Yield of Melon ( Cucumis melo  L.) in Drip Irrigation Systems Melon  (Cucumis melo L.)  is a fruit crop including the family Cucurbitaceae. Melon is not a plant native in Indonesia but can grow in the tropical region. This fruit is very popular in the community and is often used by hotels as a welcome fruit. Badan Pusat Statistik's (2019) data stated that melon production in Bali increased in 2019 to reach 552.00 tons. This study aimed to obtain the appropriate planting medium for melon cultivation by drip irrigation systems in a greenhouse. The treatments consisted of three types of planting media: husk charcoal media,  cocopeat , husk charcoal mixture with  cocopeat , and melon varieties suitable for cultivation in a greenhouse using drip irrigation. The results showed the treatment of  cocopeat  could increase the development of melons.  Cocopeat  (M c ) can be increase the yield and quality of melons, and this can be seen in the fruit weight (1,214.50 g/plant) and total dissolved solid (11.87  0 briks). Golden melon variety (Alisha F1) was able to produce sweeter fruit (11.97  0 brix), but the fresh weight was lower (887.33 g / plant).